FUNGSI DAN PERAN TRUMPET PADA COMBO BRASS BAND DALAM LAGU ADA KUASA DALAM PUJIAN KARYA JONATHAN PRAWIRA DI GEREJA BETHEL KELUARGA ALLAH YOYAKARTA - Wedha Laksana (Saraswati)
Trumpet is an important element in a big band arrangement, in this occasion trumpet present in any format and combo band brass section. Worship in Bethel Church Family of God in Yogyakarta using brass section format which will make worship becomes more colored and add to the solemn congregation. Function trumpet in the song arrangements "Ada Kuasa dalam Pujian" became one of the main goals for the author to review it. In this song played by 7 players and 5 players inflatable combo band, wind instruments such as saxophone soprano I, Alto Saxophone I, Alto Saxophone II, Trumpet I, Trumpet II, flugelhorn, trombone, while the band combo player Keyboard I, Keyboard II, Guitar , Bass Guitar, Drums. The song "Ada Kuasa dalam Pujian" in the form of songs categorized into two parts consisting of a number of bars A1B1B1 dengan AB 115 bars, using a fast tempo. In this arrangement organized into 9 sections which consist of the following elements: Introductions (intriduction), track (song), middle section (interlude) and the last section (coda). Allegro tempo used to form fusion-style. The analysis of the function of form this trumpet and the bridge is expected to stimulate the church musicians to be more active in managing the works of jazz in worship, especially the brass ensemble.   Key words: Trumpet, Brass Band, Arrangement